CEO Overconfidence, CEO Power, and Corporate Performance - Meng, Xiangsheng (2022)
Under the modern enterprise system, with the separation of ownership and control, executives are responsible for the daily operation of the enterprise. The personal characteristics of executives affect their behavioral tendencies and then affect the business choice and development direction of the enterprise, thus affecting corporate performance. Overconfidence, as a prominent representative of the irrational characteristics of executives, has been widely concerned by scholars. From the perspective of corporate governance, this paper discusses the impact of CEO overconfidence on corporate performance and adds CEO power as a moderating variable to analyze the impact of CEO power on the relation between the two, providing a reference for the development and improvement of the corporate governance system. This paper selects the listed companies covered by the US S&P 500 index from 2016 to 2021 as the research object, uses the change of CEO shareholding to measure CEO overconfidence, measures corporate performance with ROA, and sets up the empirical models. This paper uses Stata to conduct empirical analysis and draws the following conclusions. First, CEO overconfidence is negatively correlated with corporate performance. Second, CEO power positively moderates the negative correlation between the two. Finally, according to the research conclusion, this paper puts forward some recommendations, explains the shortcomings of the research, and prospects for the future research direction.